Conflict Management in Islamic Boarding Schools: The Dispute That Gave Birth to New Branches of Islamic Boarding Schools - Saefrudin Saefrudin (PT. Anagata Sembagi Education, 2026)
This study examines the phenomenon of internal conflict management in Islamic boarding schools (pesantren), which unexpectedly gave rise to new branches as a result of the dynamics of division and reconciliation within the traditional Islamic educational community in Indonesia. Through a systematic literature review of 40 scholarly sources published between 2021 and 2024, this study analyzes patterns of conflict between kiai (Islamic boarding school teachers), senior santri (students), and pesantren families; conflict resolution mechanisms based on local Islamic wisdom; and the dynamics of conflict transformation into pesantren institutional expansion. The study's results indicate that constructively managed internal pesantren conflict has the potential to become a catalyst for the proliferation of new pesantren institutions, expanding the network of Islamic education in Indonesia. The values ​​of moderation, deliberation, and the wisdom of local ulama have proven to be important instruments in the process of transforming conflict into opportunities for institutional development. The implications of this research provide a framework for developing conflict management based on Islamic values ​​that is adaptive to the needs of pesantren expansion in the modern era.